Enhancing Malaysian’s SMEs performance: leadership and innovation - Rahim, R. A. (American Scientific Publishers, 2016)
This paper formulates a framework postulated innovation as mediator in the relationship between transformational leadership style and SMEs Performance. Identifying and adopting the practice of leadership and management skills to make the organization more successful as well as creating sustainable enterprises have become an important effort for both practitioners and academics. Many literatures have assured the important attribute to sustain as successful enterprise is leadership and management skills. With good leadership practice, innovative behavior also can be encouraged among the worker then in turn boost innovation performance. The SMEs sector is an important sector, which it significantly contributes to the economic and social growth. In developing country such as Malaysia, SMEs play an essential role and have been regarded as a key driver in the nation’s progress towards internationalization. Despite the fact that SMEs has been supported by the Malaysian government, however, Malaysian SMEs still does not make sufficient progress and not achieving high performing organization. This is because of several challenges faced by SMEs. The most important challenges discussed in this paper are leader capabilities in managing human resources with good leadership practices. Innovation also one of the important success factor for SMEs and in view of that, leaders play a vital role in embedded innovative behavior among workers. Therefore, it is significant to study in this area which in turn may help the relevant parties to a better understanding of a leader’s role and what drives the innovation activities among SMEs.